PENGARUH BAURAN PEMASARAN TERHADAP KEPUASAN KONSUMEN PADA HOTEL RESTY MENARA PEKANBARU - Dwi Geno Veva; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The study is conducted at resty tower hotel pekanbaru, the purpose of this research is to find to determine marketing mix factors that influence on consumer satisfaction at Resty Tower Hotel. Marketing mix as the independent variable ( x ).Meanwhile, the customer satisfaction as dependent variable ( y ). The problem in this research is the sales in service room at resty tower hotel pekanbaru did not reach the target. The percentage of sales services seen from the hotel room with a fluctuation on purchase of services rooms within five years. The samples taken from 100 respondents from population by using formulas slovin. Data obtained from the results of a questionnaire and then processed to be tested by statistic program through spss. The results obtained from calculation is that marketing mix had positive impact on consumer satisfaction at the resty tower hotel pekanbaru. Kata Kunci : Marketing Mix, Costumer Satisfaction, and Resty Hotel